2012
DOI: 10.1177/0363546512454414
|View full text |Cite
|
Sign up to set email alerts
|

Survival of the Anterior Cruciate Ligament Graft and the Contralateral ACL at a Minimum of 15 Years

Abstract: Fifteen years after ACL reconstruction, expected survival of the ACL graft was 89% and expected survival of the CACL was 86%. Graft choice did not affect ACL graft rupture, but using BPTB increased the risk of CACL rupture compared with HT. Men had a less favorable survival rate of the ACL graft than did women, and a family history of ACL rupture increased the risk of both ACL graft and CACL rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
217
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(237 citation statements)
references
References 22 publications
17
217
1
2
Order By: Relevance
“…Shelbourne et al found that a young age increased the risk of ACL graft rupture [42], whilst Bourke et al did not find an effect of age, but did find that male gender and a positive family history of ACL injury were associated with an increased risk of ACL graft rupture [9]. It is not clear whether it was youth per se that was associated with an increased risk in the study by Shelbourne et al or whether youth was a surrogate for other factors such as increased activity, increased risk-taking or incomplete neuromuscular development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shelbourne et al found that a young age increased the risk of ACL graft rupture [42], whilst Bourke et al did not find an effect of age, but did find that male gender and a positive family history of ACL injury were associated with an increased risk of ACL graft rupture [9]. It is not clear whether it was youth per se that was associated with an increased risk in the study by Shelbourne et al or whether youth was a surrogate for other factors such as increased activity, increased risk-taking or incomplete neuromuscular development.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear whether it was youth per se that was associated with an increased risk in the study by Shelbourne et al or whether youth was a surrogate for other factors such as increased activity, increased risk-taking or incomplete neuromuscular development. With regard to contralateral ACL rupture, female gender [42] and a positive family history, a return to pre-injury sport and an ACL reconstruction with a patellar graft [9] have been identified as risk factors, although there are also studies that did not identify gender as a risk factor [37,50]. One study identified a young age as a important risk for contralateral ACL rupture, despite it not being a risk factor for ACL graft rupture in that particular series [20].…”
Section: Discussionmentioning
confidence: 99%
“…A more effective triage system within various national and international healthcare delivery systems should be developed so high-risk populations are diagnosed and treated in a timely manner. Finally, we must develop more effective return to play assessments following ACL reconstruction, as the data demonstrates unacceptably high rates of ipsilateral and contralateral injuries in this high-risk group of athletes [2,9,10,14,15].…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…Overall, rates of sustaining a graft re-rupture or contralateral ACL rupture 15 years after primary ACLR are as high as one in every four individuals (Bourke, Salmon, Waller, Patterson, & Pinczewski, 2012). Additionally, reported rates of re-revision ACLR at an average five years after revision ACLR range from four to five per-cent (Leroux et al, 2014;Lind et al, 2012).…”
Section: Subsequent Injury and Revision Surgerymentioning
confidence: 99%
“…Of further concern is that as many as 1 in 5 ACL-reconstructed individuals undergo subsequent knee surgery within 6 years of ACLR (Hettrich et al, 2013) and 1 in every 4 individuals may experience an ACL graft rupture or contralateral ACL rupture within 15 years of ACLR (Bourke et al, 2012).…”
Section: Introductionmentioning
confidence: 99%